The effect of competitive and cooperative play on learning difficulties for (7-8) years children - Nazar, Taraq (Journal of Physical Education, 2013)
The aim of the project was to study the degrees of difficulties of learning for children (7-8) years and the possibilities of decreasing these difficulties by using competitive and cooperative play. The subjects were (63) second grade students at Ansam Elementary School in Baghdad . Those students were divided into three groups : Two experimental groups(competitive and cooperative) ,and one control group (enrolled in regular physical education class). 16 sessions were administered for all three groups. Results showed significant decrease of learning difficulties for both experimental groups compared to the control group. The researcher recommended the use of competitive ,cooperative, and other kinds of play to reduce learning difficulties for children. He also recommended doing similar studies for other samples and other kinds of play